Controle da reação do solo e adubação fosfatada na produção e pós-colheita de melão Cantaloupe - Silva, Ana Cláudia da (2018)
Pre-harvest stages, such as soil management and mineral nutrition, just as post-harvest storage, are of great importance for the production, quality and useful life of the fruits in the melon crop. In this sense, the objective of this research was to study the control of soil reaction and phosphate fertilization in the production and post-harvest of Cantaloupe melon when stored under refrigeration and modified atmosphere. For this, two experiments were performed, one with Cantaloupe Hy melon and the other with Florentine melon, in which both had one phase in the field and another in the laboratory. The experiment was carried out in a randomized complete block design, with 3x2 subdivided plots, three types of acidifiers in the plots (sulfur, sulfuric acid and without acidifier), and in the subplots two phosphorus doses (50 and 150 kg ha-1 of P2O5) with four replicates. The treatments were: T1 (without acidifier + 50 kg ha-1 P2O5), T2 (without acidifier + 150 kg ha-1 P2O5), T3 (sulfuric acid + 50 kg ha-1 P2O5), T4 + 150 kg ha-1 of P2O5), T5 (sulfur + 50 kg ha-1 of P2O5) and T6 (sulfur + 150 kg ha-1 of P2O5). The doses of the acidifiers provided pH control of the soil to around 6.5. For the acid, the dose used was 0.5 L/m3 of soil and for the sulfur the dose was 1000 kg ha-1 of soil to lower the pH to 6.5. Commercial sulfuric acid (14N) was used. In the laboratory, the experimental design was in randomized blocks, in a scheme of sub-divided plots 3x2x4 for Hy mark melon, and 3x2x5 for Florentino melon, in which the plots were acidifying; (0, 7+3, 14+3 and 21+3), and (0, 7+3, 14+3, 21+3 and 28+3), the subplots the doses of phosphorus and, the subsubparcels, storage times) days, respectively. The refrigerated storage was (5±2 ºC and 90±2% RH) + three days at a temperature of 23±2 ºC and 60±2% RH. We analyzed: Soil pH, EC, phosphorus, commercial and total productivity, number of fruit / commercial and total plant, commercial and total average mass, vitamin C, mass loss, external and internal appearance, pH, pulp color, pulp firmness, titratable acidity, soluble solids, soluble solids / titratable acidity ratio, total sugars and total carotenoids. For the Hy mark melon, the sulfur provided better results from the production components and the sulfuric acid improved the quality of the fruits, considering some parameters. Regardless of the treatments studied, the quality characteristics remained within the standards demanded by the consumer market until the 24 days of storage. For Florentine melon, the 150 kg ha-1 dose of P2O5 provided a better melon yield, compared to the dose of 50 kg ha-1. Regardless of the treatments studied, fruit quality remained within acceptable standards up to 31 days of storage according to internal and external appearance. The 150 kg ha-1 dose of P2O5 provided higher values of chroma in the fruits and the sulfuric acid provided higher carotenoid content of the fruits